2003
DOI: 10.1002/ceat.200303040
|View full text |Cite
|
Sign up to set email alerts
|

Morphology Development of Polymer Blends in Complex Flow Fields

Abstract: Communications even in case of mercury peaks in the raw gas. As a functional alternative to the MercOx process, an acid and alkaline scrubber, a carbon-entrained bed reactor, and a fabric filter can be combined to remove the flue gas components listed above. In the case of the MercOx process, however, investment costs are far smaller, due to its reduced technical expenditure. Hydrogen peroxide represents a comparably inexpensive oxidant. This and the fact that a small pressure drop only is generated in the Mer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…However, different studies have revealed that the properties of such immiscible blends can be significantly improved by the addition of a suitable compatibilizer during blending [22][23][24][25]. Copolymer-containing segments, chemically identical to the individual homo polymers, are generally employed as compatibilizers [26][27][28][29]. The analysis of the vapor permeation through such a compatibilized blend can provide interesting information on different types of interactions existing therein and information on the morphology [30].…”
Section: Introductionmentioning
confidence: 98%
“…However, different studies have revealed that the properties of such immiscible blends can be significantly improved by the addition of a suitable compatibilizer during blending [22][23][24][25]. Copolymer-containing segments, chemically identical to the individual homo polymers, are generally employed as compatibilizers [26][27][28][29]. The analysis of the vapor permeation through such a compatibilized blend can provide interesting information on different types of interactions existing therein and information on the morphology [30].…”
Section: Introductionmentioning
confidence: 98%